(untitled) (Docentes 2.0 Journal, 2023)
The evaluation, whose concept has changed, is important in teaching. There is no longer talk of measuring student performance based on a grade. This work aimed to investigate the impact of this new modality of evaluation in primary education through a systematic review of the literature applying the PRISMA method and collecting 45 articles from the search in databases such as Scielo and Scopus. This research was based on the analytical method, positivist paradigm, qualitative approach, and topical narrative design, as well as being of an informative and cross-sectional documentary type. From this review, it has been shown that formative assessment has many benefits to achieving learning, both for students and teachers. At the same time, it explores the training required for a teacher, as the great responsibility of implementing formative evaluation falls on him. Finally, it is concluded that it promotes the development of student competencies, which allow them to achieve learning achievement. Through this evaluation process, students and teachers are motivated to continue on the path of learning.